ANALISIS MESIN ANJUNGAN DUKCAPIL MANDIRI (ADM) DALAM MENINGKATKAN KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DISDUKCAPIL KOTA SEMARANG - Muhammad Abdurrozaq; Bangkit A. Wiryawan (Journal of Politic and Government Studies, 2026)
Digital transformation in population administration services has encouraged local governments to adopt technology-based innovations such as the Population and Civil Registration Self-Service Kiosk (Anjungan Dukcapil Mandiri/ADM) to improve public service quality, although its implementation has not yet been fully optimized in practice. This study examines the implementation of ADM in enhancing the quality of population administration services at the Department of Population and Civil Registration (Disdukcapil) of Semarang City, as well as identifying the constraints affecting its effectiveness. The research employs a qualitative descriptive approach, with data collected through interviews with officials from the Population Administration Information Management (PIAK) division, ADM operators, and 1Mahasiswa Ilmu Pemerintahan Universitas Diponegoro 2Dosen Ilmu Pemerintahan Universitas Diponegoro service users, supported by observation and documentation, and analyzed using service quality dimensions. The findings indicate that ADM implementation contributes to improving service efficiency, expanding public access to self-service document printing, and accelerating digital based administrative processes. However, service optimization remains constrained by several factors, including technical issues in systems and devices, limited public understanding of ADM services, suboptimal utilization of electronic ID card (e-KTP) printing features, and the continued concentration of service usage at the main Disdukcapil office. These findings suggest that the success of ADM implementation is determined not only by technological readiness but also by institutional capacity, effective socialization strategies, and the level of public participation in supporting digital-based public service governance.